Philanthropic-crowdfunding-partnership: A proof-of-concept study for sustainable financing in low-carbon energy transitions - Ibrahim Ari (12058516) (2021)
This study presents a proof-of-concept focusing on sustainable crowdfunding models for renewables as alternatives to conventional financing instruments and proposes a Philanthropic-CrowdfundingPartnership (PCP) model. In this regard, this research investigates social welfare by evaluating the change in wealth inequality for the future time horizon by simulating conventional and the PCP financing models on solar farms in the case study of Turkey. The motivation is to find a solution for financing regional development in a holistic approach considering society and the environment to accomplish sustainable development. Furthermore, it also aims to provide insights into innovative public-private partnerships to unlock new horizons for development by incorporating citizen participation at large. The PCP model’s objective is to mobilize capital throughout the public by prioritizing individuals along with small and medium enterprises over the large corporates in fundraising for renewable energy projects, mainly solar farms. This paper provides quantitative evidence that the PCP functions as a sustainable and alternative financing model by dramatically reducing wealth inequality. Besides, the PCP holds the potential to become a self-sufficient financing mechanism for projects ranging from small ones to mega initiatives. Other Information Published in: Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.energy.2021.119925